Discovering Art History - Brommer, Gerald F.; Kohl, David (Worcester, Massachusetts: Davis Publications, 1988)
A textbook covering the world and work of the artist, trends and influences in world art, and art in the western world.
Includes index.
Bibliography (p. 529-530).
Keywords: Art -- History -- Juvenile literature; Art appreciation -- Juvenile literature; Art -- History; Art appreciation